An exercise in analysis as enjoyment. Issue 12 (2nd December 2022) - You, Mia
ABSTRACT: Gertrude Stein and, consequently, Adam Frank's Radio Free Stein project underscore the potentiality of enjoyment as a mode of analysis and knowledge. This paper considers the complex nature of enjoyment – regarding it a generative form of struggle, appreciation and, in Stein's words, 'making a fuss' – and positions it as a radical challenge to the current data-driven mode of flattening aesthetic judgment to 'like' or 'dislike'. The Radio Free Stein project also functions as a case study for the value of artistic research and how artistic research either might align with or provide an alternative to the model of 'scientific research' in the university. Finally, this paper employs theoretical descriptions of listening from Roland Barthes, Pauline Oliveros and Charles Bernstein to propose varying methods of enjoying (and understanding) Radio Free Stein's two recordings of Stein's 1917 play 'An Exercise in Analysis', composed by Dan Warner.